Effect of Pesticide Poison on Post-Mortem Interval Determination Based on Entomological Study - Barizah Luay Widyana (Jurnal Biosains Pascasarjana, 2023)
Determination of post-mortem intervals (PMI) is a major key in forensic investigation. On the discovery of a decomposed corpse, a post mortem examination is difficult. PMI can be made by observation of insects that appear around the corpse, called forensic entomology. Forensic entomology carried out by analyzing the species of larvae and calculating the age of insects so that the time of death can be estimated. Forensic entomology has been developed in toxicological examinations so that insects found can be used as toxicological samples. The cause of death can be due to poisoning. Poisons often used in case of poisoning or suicide is pesticides. This research is a Systematic Review, a study that takes and collects data from various previous studies related to the chosen theme. The study was conducted according to protocol and registration with reference to PRISMA and JBI. Literature searches are obtained from online databases. The results were obtained by 21 studies after selection and elimination in accordance with protocol. The most accurate determination of the post mortem interval depends on post-death changes and the decomposition process. Some types of pesticides can cause the decomposition process to take place faster but some other types of pesticides can slow down the decomposition process. The content of toxins in the body ingested has an effect on the development and growth of necrophagous insects. The growth of flies will be stunted or even stopped, the presence of toxins in the corpse can be a contributing factor in the determination of the post-mortem interval. Deaths caused by toxins still need to be further researched because different types of toxins can show different side effects on the body.